STRENGHTS AND WEAKNESSES OF WRITING MATERIALS FOR UNIVERSITY STUDENTS OF EX-KARESIDENAN SURAKARTA - Rini Fatmawati (Universitas Muhammadiyah Semarang, 2015)
Writing lecturer has no enough knowledge as to the writing material development. He is usually as a writing material provider, not a writing material developer. This study is aimed at describing the weaknesses and the strengths of the writing materials used at the beginning semester of University of ex-Karesidenan Surakarta. The data are the teaching materials of writing used at it; collected by the document analysis, observation, and interview; and the step of analysis is data collection, data reduction, data display, and conclusion. The research result is that writing materials at the one of UMS belong to the point chosen from writing skill, belong to the writing skills, writing skill is learned after reading skill, and cannot be the base for learning the ones in the next semester; the ones at UNS can be the base for it, do not belong to the point chosen from it, some of which do not belong to them, and it is learned before it; and the ones at UNIVET, UNISRI and UNWIDA belong to the point chosen from it, cannot be the base for it, some of which do not belong to them, and it is learned before it.Keywords: writing skill, material